The problem of morality in the Manichaean cosmological and soteriologic system - Nunes Costa, Marcos Roberto (Anales del Seminario de Historia de la Filosofía, 2004)
Manicheism is founded in two world originating ontological principles: Good or Light, presented by the sun and Evil or Darkness, personinified in the matter. From this ontological dualism proceeds the idea which man is not responsible to the evil he practices according to, but this-one (evil) is to be blamed to his bad nature, in other words evil is inherent to his corporal nature. Hence, strictly speaking, there is no real evil in manicheism, but only natural evil. However, paradoxally, manicheism refers to a duty Moral, which through the man good part (the soul) must struggle in order to be liberated from matter´s bonds (the boddy), through an ascetical rigorous life, materialized in three commandments observance, the to called three seals: mouth, hands and breast seals.